KEPEMILIKAN PERENCANAAN KEUANGAN HARI TUA PADA PEKERJA KOTA BOGOR - Rizky Amelia; Hartoyo Hartoyo; Budi Suharjo (MIX: JURNAL ILMIAH MANAJEMEN, 2017)
Abstract. This study aims to analyze the influence of attitude toward behavior,subjective norms, and perceived behavioral control on Bogor‟s employee. This study isaims too to analyze the demography characteristic of Bogor‟s employee who haveretirement planning. This study was conducted on 97 Bogor‟s employee and wasconducted in August until October 2016. The results of logistic regression showed thatthe indicators of subjective norms and perceived behavioral control have positive effecton financial retirement planning to Bogor‟s employee. Research also showed thatownership of financial retirement planning tend to be owned by the city of Bogor‟semployee who have more than one number of dependents, aged over 30 years old,married, and earning over nine million per month.Keywords: retirement planning, theory of planned behavior, employee in Bogor